"Bhakti" or "love" in the school of Ramanuja and Mawlana - Afroogh, Mohammad Reza (Revista de cultura teológica, 2018)
In the mystical worldview, the word “love” denotes a broad and multilayered concept. Most mystics from different nations regard love as one of the basic principles and lessons in the world of mysticism. Many of them have pledged underlying conditions in the path of conduct and achievement to the position of knowledge and certainty of majesty of God to the elixir of love. In the school of Mowlana, love has a high status, and human perfection is possible by recognizing the Imam or leader in the combination of love. On the other hand, most Indian schools were influenced by “Bhakti Marga”, which was more prominently displayed in the Ramanuja School, as it grew in the works of South India and Tamil, and as the “New Age” movement continued. Therefore, in this article, we are going to examine the comparative approach of this concept based on Rumi’s poems and the teachings of Ramanuja. In fact, our aim is to analyze the mutual and different views of both mystics on love and its nature.